Enteral nutrition of the premature infant - Su Jin Cho (Korean Pediatric Society, 2010)
Early nutritional support for preterm infants is critical because such support influences long-term outcome. Minimal enteral feeding should be initiated as soon as possible if an infant is stable and if feeding advancement is recommended as relevant to the clinical course. Maternal milk is the gold standard for enteral feeding, but fortification may be needed to achieve optimal growth in a rapidly growing premature infant. Erythromycin may aid in promoting gastrointestinal motility in cases that exhibit feeding intolerance. Selected preterm infants need vitamins, mineral supplements, and calorie enhancers to meet their nutritional needs. Despite all that is known about this topic, additional research is needed to guide postdischarge nutrition of preterm infants in order to maintain optimal growth and neurodevelopment.